1990
DOI: 10.1002/ijc.2910460307
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for hepatocellular carcinoma in catalonia, spain

Abstract: The influence of hepatitis B virus infection, alcohol consumption, tobacco smoking and use of oral contraceptives on the risk of hepatocellular carcinoma (HCC) was evaluated in a hospital-based case-control study in Catalonia, in the Mediterranean coastal area of north-eastern Spain. A total of 96 HCC cases (86.5% of them with associated liver cirrhosis) and 190 age- and sex-matched controls were studied. The odds ratio of HCC and 95% confidence interval among hepatitis B surface antigen (HBsAg) carriers was 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
27
0

Year Published

1992
1992
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(28 citation statements)
references
References 29 publications
1
27
0
Order By: Relevance
“…No association between cigarette smoking and HCC was evident in the Brescia HCC study, even when restricting the analysis to subjects negative for HBV and HCV infection and alcohol consumption (Gelatti et al, 2005b), although a limit of the study was the small number of HCC subjects negative for all the main risk factors for the disease. No role of tobacco smoking was found also in two small casecontrol studies carried out in Greece and Spain (Vall Mayans et al, 1990;Hadziyannis et al, 1995). Among some large cohort studies performed in East Asia, a few showed an increased risk of death from liver cancer among smokers compared to non-smokers (Goodman et al, 1995;Liaw and Chen, 1998;Liu et al, 1998;Mizoue et al, 2000), but those that took account of HBV and HCV infection and alcohol intake did not find the association (Mori et al, 2000;Evans et al, 2002;Sun et al, 2003).…”
Section: Tobacco Smokingmentioning
confidence: 96%
“…No association between cigarette smoking and HCC was evident in the Brescia HCC study, even when restricting the analysis to subjects negative for HBV and HCV infection and alcohol consumption (Gelatti et al, 2005b), although a limit of the study was the small number of HCC subjects negative for all the main risk factors for the disease. No role of tobacco smoking was found also in two small casecontrol studies carried out in Greece and Spain (Vall Mayans et al, 1990;Hadziyannis et al, 1995). Among some large cohort studies performed in East Asia, a few showed an increased risk of death from liver cancer among smokers compared to non-smokers (Goodman et al, 1995;Liaw and Chen, 1998;Liu et al, 1998;Mizoue et al, 2000), but those that took account of HBV and HCV infection and alcohol intake did not find the association (Mori et al, 2000;Evans et al, 2002;Sun et al, 2003).…”
Section: Tobacco Smokingmentioning
confidence: 96%
“…~-9 Seven of these were conducted in Western countries with low incidence of HCC, [1][2][3][4][5]7,9 and two in developing countries with a relatively high incidence of this tumor. 6,8 In all the studies in developed countries as well as the South African study, 8 an increased risk for HCC was found among OC users, although no such association was evident in the WHO collaborative study which was undertaken in populations of several developing countries?…”
Section: Introductionmentioning
confidence: 99%
“…Although HCC is a typical viral infection-related malignancy derived from chronic hepatitis B and C [2][3], HCC has also been strongly associated with lifestyle. Excessive alcohol consumption, obesity and type 2 Research Paper www.impactjournals.com/oncotarget diabetes are strongly associated with the carcinogenesis and development of HCC [4][5][6][7]. Thus, not only the proportion but also the number of HCC patients with nonviral etiologies has been increasing on a global scale [2].…”
Section: Introductionmentioning
confidence: 99%